Pseudotomodon trigonatus, False Tomodon Snake - Arzamendia, Vanesa (2016)
Listed as Least Concern because extent of occurrence, number of locations, and population size are relatively large, and because the species probably is not declining fast enough to qualify for any of the threatened categories.